PENDIDIKAN DAN KEPEMIMPINAN WANITA DALAM PERSPEKTIF AL QURAN DAN SUNAH - Iyoh Mastiyah (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
Theologically speaking, women are the `khalifah' on earth, having equal positions, rights and responsibilities to men, both in the field of `ibadah' and social life. Women as housewives (mothers) in the family have significant role in building and guarding the integrity of thelam* and so do the men. In both the family and social life, men and women's roles are not more dominant than the others; both men and women share equal responsibilities. Furthermore, there is no restriction for women to work as professional workers or leaders as long as they are able to bring about benefits for themselves, the family as well as the society. This article will provide theological arguments on the fact that Islam never puts any restriction on women's activities as long as those activities are carried out in the spirit of Islamic values.